Comparison of fruit organic acids and metabolism-related gene expression between Cerasus humilis (Bge.) Sok and Cerasus glandulosa (Thunb.) Lois. - Xiaopeng Mu (PLoS ONE, 2018)
Cerasus humilis (Bge.) Sok and Cerasus glandulosa (Thunb.) Lois are economically important fruit-producing shrubs. Although these two species have similar looking fruits, their fruit organic acid contents differ drastically. In this study, we focused on comparing the organic acid content, activity of enzymes gene expression involved in organic acid metabolism in both C. humilis and C. glandulosa fruits. To investigate the differences of organic acid metabolism in fruits of these two species, a comparative transcriptome analysis was performed. Our results showed that temporal changes of two main organic acids exhibited different trends in these two species. Transcriptome sequencing of developing C. humilis and C. glandulosa fruits systematically revealed 6,594 differentially expressed genes. Compared with C. humilis, the expression levels of 3,469 and 3,125 genes were up- and down-regulated in C. glandulosa, respectively, including one PEPC gene, 12 malic acid metabolism genes, 25 citric acid cycle genes, and 194 NAD/NADP metabolism genes. The correlation analysis and principal component analysis of gene expression, enzymatic activity and organic acid content showed that differences in the expression of genes encoding the NAD-malate dehydrogenase (NAD-MDH) and NADP-malate enzyme (NADP-ME) contributed substantially to the observed differences in organic acid accumulation of two species. Our results provide a solid foundation for future elucidation of key mechanisms regulating organic acid biosynthesis in C. humilis and C. glandulosa fruits and could lead to efficient and highly targeted generation of more commercially accepted cultivars.